A novel P‐S‐Si‐based cage‐structural monomer for flame‐retardant modification of unsaturated polyester resin. (27th December 2020) - Zhang, Gang; Song, Dongdong; Ma, Su; Wang, Yanlin; Xie, Xiaotian; Dong, Yanmao
Abstract : Currently, the issue of improving the flame‐retardant performance of unsaturated polyester resin (UPR) has drawn a lot of attention. In this study, methyl vinyl di (1‐thio‐2, 6, 7‐trioxal‐1‐phosphabicyclo [2.2] octane‐4‐methoxy) silane (MVDOS) with P‐N‐Si‐based cage unit was synthesized, and it was utilized as a reactive flame‐retardant monomer to modify UPR. The UPR/MVDOS composites were prepared by introducing different ratios of MVDOS into UPR via the reaction of crosslink. The efficiency of the resulted composites was investigated by using the limiting oxygen index (LOI), vertical burning test, and cone calorimeter test. The results showed that the composites reached the V‐0 rate without dripping, and the LOI value was 29.1% when the content of MVDOS was as low as 18 wt%. Cone calorimeter tests revealed the peak of heat release and CO production of UPR/MVDOS‐18 were 238.2 KW/m 2 and 0.0167 g/s, which were respectively lower than the ones of neat UPR. The introduction of MVDOS also increased the stability of UPR composites. Furthermore, the scattering electron microscopy, laser Raman spectroscopy, and X‐ray photoelectron spectroscopy studies revealed that the incorporation of MVDOS stimulated the UPR matrix to generate char layer with increased graphitization degree, which provided a good barrier to prevent heat and oxygen from being transferred and then protected the materials inside from further burning. This research provides a new way to obtain flame‐retardant UPR composites with high performance.